Risk factors of breast cancer in Dezful city of Iran: a case-control study - Behzad Jafarinia (Tehran University Medical Journal, 2016)
Background: Breast cancer is one of the most prevalent cancers among women and features increasing trends of incidence rates. Worldwide, yearly about 1.67 million of new cases and 522,000 of deaths from breast cancer are registered. The aim of this study was to determine the risk factors of breast cancer in women and to identify high risk groups.